Hajj Financing Transparency in Islamic Cooperatives: Evidence from KSPPS Artha Bahana Syariah - Nasiroh, Fandilatun; Aini, Qurotul; Fitriyani, Yeny (Universitas Trunojoyo Madura, 2025)
Transparency in the management of Hajj bailout funds is a crucial aspect for Islamic financial institutions to enhance customer trust and understanding of the contracts used. However, in practice, there are still challenges in conveying information related to costs, contract mechanisms, and the inherent risks of this financing scheme. This study aims to analyze the implementation of transparency in Hajj funds at KSPPS Artha Bahana Syariah and to examine the institution’s compliance with Islamic accounting standards, particularly PSAK 107.This research employs a qualitative method with a transparency-based approach to analyze information disclosure in Hajj bailout financing. Data were collected through in-depth interviews, direct observations, and document analysis related to Hajj bailout financing. A triangulation technique was applied to ensure the validity of the data obtained.The findings indicate that transparency in Hajj funds at KSPPS Artha Bahana Syariah still faces obstacles, especially in delivering information concerning costs and risks to customers. Although the institution has attempted to apply Sharia principles through the ijarah contract, improvements in information disclosure are still needed to align with PSAK 107 and enhance customer trust.The benefits of this research include providing strategic input for KSPPS and other Islamic financial institutions in strengthening the implementation of transparency principles, particularly in Hajj funds. The practical implications suggest that this study can serve as a reference for regulators, academics, and Islamic finance practitioners in developing guidelines and policies that support greater information disclosure and compliance with Islamic accounting standards.